Aberrometric, Keratometric, and Visual Outcomes After Trans-Epithelial Topography-Guided Phototherapeutic Keratectomy for the Treatment of Irregular Corneas - Cano-Ortiz A; Morales P; Sánchez-Ventosa; Leiva-Gea I; Membrillo A; Druchkiv V; González-Cruces T; Sánchez-González JM; Beltrán J; Villarrubia A (Clinical Ophthalmology, 2021)
Antonio Cano-Ortiz,1 Pablo Morales,2 Álvaro Sánchez-Ventosa,1 Isabel Leiva-Gea,3,4 Alberto Membrillo,1,5 Vasyl Druchkiv,6,7 Timoteo González-Cruces,1 José-María Sánchez-González,8 Jaime Beltrán,7 Alberto Villarrubia1 1Instituto de Oftalmología la Arruzafa, Córdoba, Spain; 2Department of Cataract and Refractive Surgery, Clínica Baviera, Málaga, Spain; 3Hospital Regional Universitario de Málaga, Málaga, Spain; 4Istituto de Biomedicina de Málaga (IBIMA), Málaga, Spain; 5Universidad de Córdoba, Córdoba, Spain; 6University Medical Center Hamburg Eppendorf, Hamburg, Germany; 7Department of Research & Development, Clínica Baviera, Valencia, Spain; 8Department of Physics of Condensed Matter, Optics Area University of Seville, Seville, SpainCorrespondence: Pablo Morales; Isabel Leiva-Gea Málaga, SpainTel +34 669 232 767; Tel +34 677254051Email pblmorales@hotmail.com; isabeleiva@hotmail.comPurpose: To assess the safety, aberrometric and keratometric changes, and stability of trans-epithelial topography-guided phototherapeutic keratectomy (TE-TG-PTK) with mitomycin C (MMC) using the ALLEGRO Topolyzer platform for the treatment of irregular astigmatism.Methods: This is a retrospective case series including 57 eyes that underwent TE-TG-PTK + MMC using the ALLEGRO Topolyzer platform for the treatment of irregular astigmatism. CDVA, manifest refraction (MR), keratometry readings, and aberrometry readings were analyzed at 1, 3, 6, and 12 months.Results: Causes of corneal irregularity included non-infectious leucoma (n=23), infectious leucoma (n=7), adenoviral keratitis (n=20), corneal haze (n=2), post-penetrant keratoplasty (PKP) (n=1), and others (n=4). Overall, 76% of the eyes (n=40) gained lines of vision; patients gained 1, and 2 or more lines of vision in 76%, and 38% of cases, respectively. Only 1 patient (2%) lost 5 lines of vision. Mean preoperative CDVA (LogMAR) was 0.37 ± 0.31 and improved to 0.14 ± 0.18 (p< 0.001) at final follow-up (12 months). CDVA remained unchanged in 10 eyes (21%). No significant changes were observed in mean keratometry (Kmean) and keratometric astigmatism readings. Regarding aberrometry, only changes in coma proved to be significant 6 months after surgery (P< 0.01). No intraoperative/postoperative complications were reported.Conclusion: At final follow-up, significant improvements were observed in CDVA and coma. TE-TG-PTK + MMC proved to be an effective and safe procedure for the treatment of corneal irregular astigmatism due to several causes.Keywords: topography-guided phototherapeutic keratectomy, irregular astigmatism. laser refractive surgery, mitomycin C